Study of the relationship between the amount of reliable precipitation in Poland with external parameters - Licznar, Paweł; Siekanowicz, Katarzyna; Oktawiec, Michał (Instal, 2019)
The research presents results on application possibility of external parameters, such as: average annual precipitation, coordinates of elevation in spatial estimation of maximum rainfall values. Rainfall maxima were selected from 30-year time series, recorded by 100 rain gauges in Poland. The analyses were conducted as a part of the implementation of the project: “Polish Atlas of Rainfall Intensities – PANDa”. In the introduction part there is a review of spatial estimation methods of design rainfall depths, which have been used in Poland and abroad (in Germany and in the USA) so far for rainfall national atlases and formulas. The relationships between analysed external parameters and the design rainfall amounts were evaluated using Spearman’s rank correlation coefficient for 480 rainfall maximums (for 16 durations – from 5 to 4320 minutes and 30 positions in series). Moreover, the relationship between design rainfall amount and the geographical location was verified using multiple linear regression.